Inheritor - Cherryh, C. J. (Cherryh, C. J. Foreigner universe., 1996)
Six months have passed since the reappearance of the starship Phoenix<U+2014>the same ship which brought a colony of humans to the hostile environment of alien atevi nearly two hundred years ago. During these six months, the atevi have reconfigured their fledgling space program in a bid to take their place in the heavens alongside humans. But the return of the Phoenix has added a frighteningly powerful third party to an already volatile situation, polarizing both human and atevi political factions, and making the possibility of all-out planetary war an even more likely threat. On the atevi mainland, human ambassador Bren Cameron, in a desperate attempt to maintain the peace, has arranged for one human representative from the Phoenix to take up residence with him in his apartments, and for another to be stationed on humanity's island enclave. Bren himself is unable to return home for fear of being arrested or assassinated by the powerful arch conservative element who wish to bar the atevi from space. Responsible for a terrified, overwhelmed young man, and desperately trying to keep abreast of the atevi associations, how can Bren possibly find a way to save two species from a three-sided conflict that no one can win?